If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12a + 14b + -19a = 0 Reorder the terms: 12a + -19a + 14b = 0 Combine like terms: 12a + -19a = -7a -7a + 14b = 0 Solving -7a + 14b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-14b' to each side of the equation. -7a + 14b + -14b = 0 + -14b Combine like terms: 14b + -14b = 0 -7a + 0 = 0 + -14b -7a = 0 + -14b Remove the zero: -7a = -14b Divide each side by '-7'. a = 2b Simplifying a = 2b
| (6n-25)=(3n+20) | | 8p+16+4p= | | 13x-5=5x+9 | | 7x-16=6x+7 | | 6Y-14=24 | | -3.9x+2.1=-2.4x+2.4 | | h(2)=9x^2+4 | | X+(x+1)=-27 | | -(2b+8)=2b-24 | | 3+(-7)=(-7)+3 | | x+2(-3)=-1 | | -1.9-6x=13.7 | | 4x+1.2-2.4x=0.4x-4.2 | | 19x-8-3x=15x-19 | | 12x-48+6x= | | 5a+4b*2=8x-1 | | -4(8m-8)-8m=-288 | | 2(15)=-2x+2 | | 9r-36+18= | | 2x=12+x+2 | | (2n+32)=(4n-2) | | 4(x+1)=17 | | -4(1+5n)=-124 | | sin(3x+40)sin(3x+10)=0.4 | | 10x-8-3x=15x-19 | | 16q+16+6q= | | -5(4x+1)=13 | | -3(8p+2)-2(3-23p)=3(9+7p) | | (3r+8)=(2r+12) | | 6-3s= | | 34c=3 | | 2x^2=289 |